Case-Based Reasoning Research and Development 22nd International Conference, ICCBR 2014, Cork, Ireland, September 29, 2014 - October 1, 2014. Proceedings - Lamontagne, Luc.; Plaza, Enric; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 21st International Conference on Case-Based Reasoning Research and Development (ICCBR 2014) held in Cork, Ireland, in September 2014. The 35 revised full papers presented were carefully reviewed and selected from 49 submissions. The presentations cover a wide range of CBR topics of interest both to researchers and practitioners including case retrieval and adaptation, similarity assessment, case base maintenance, knowledge management, recommender systems, multiagent systems, textual CBR, and applications to healthcare and computer games.
What I Talk About when I Talk About CBR -- Running with Scissors: Cut-Ups, Boundary Friction and Creative Reuse -- Learning Solution Similarity in Preference-based CBR -- Case-Based Parameter Selection for Plans: Coordinating Autonomous Vehicle Teams -- Automatic Case Capturing for Problematic Drilling Situations -- Algorithm for Adapting Cases Represented in a Tractable Description Logic -- Sentiment and Preference Guided Social Recommendation -- A Hybrid CBR-ANN Approach to the Appraisal of Internet Domain Names -- Further Experiments in Opinionated Product Recommendation -- How Much Do You Trust Me? Learning a Case-Based Model of Inverse Trust -- Tuuurbine: A Generic CBR Engine Over RDFS -- How case-based reasoning on e-community knowledge can be improved thanks to knowledge reliability -- Case-Based Object Placement Planning -- On the Role of Analogy in Resolving Cognitive Dissonance in Collaborative Interdisciplinary Design -- Case-Based Prediction of Teen Driver Behavior and Skill. Adapting propositional cases based on tableaux repairs using adaptation knowledge.
Keywords: Computer science; Data mining; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Application software; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computer Appl. in Administrative Data Processing; Electronic books